Does Domestic Work Affect the Academic Performance of Girls in Primary School in Côte d'Ivoire? Empirical Evidence from Probit Model - Pokou Edouard Abou (European Scientific Journal, 2016)
The objective of this paper is to highlight the effects of domestic work of girls on their school results in Cȏte d'Ivoire. From a probit model, the analysis indicates that domestic work favours, meaningfully, the fact about repeating a school year for the girl child. Besides, the availability of basic services in schools significantly reduces failure of girls in schools in rural areas. Thus, policy makers must equip schools with canteens, toilets for girls, and they should also provide the necessary facilities for drinking water points.
Keywords: 330; Domestic work; quality of school; probit; school results; Côte d'Ivoire